위장조영검사에 대한 의료서비스 만족도에 관한 연구 - 김규형(Gyoo-Hyung Kim); 임청환(Cheong-Hwan Lim) (한국콘텐츠학회 논문지, 15(3), 2015)
This study was conducted with examinees who chose upper gastrointestinography (UGI) among those who visited the hospital for health examination in order to improve the visitors' satisfaction with services. A questionnaire survey was conducted with the examinees, and 147 examinees who visited the hospital during the two months from May 2014 participated in the survey as the subjects of pre education examination while 164 examinees who visited during the months from July 2014 participated as the subjects of post education examination. The pre education subjects were surveyed about anxiety, need of explanation, method of explanation, satisfaction with UGI, etc., and a video was prepared based on the results and provided to the post education subjects and then they were surveyed about change in anxiety, satisfaction with the explanation in the video, helpfulness of the video, intention to watch the video again, etc. In the pre education survey, the average value of anxiety was 2.62, and the need of explanation was 2.52, In addition, 78.2% of the subjects chose guide video as a method of explanation, and satisfaction with UGI was 1.55. In the post education survey, the average value of changed anxiety was 1.45, satisfaction with video explanation was 2.80, helpfulness was 2.79, and intention to watch the video again was 2.80. In the results of T-test between the pre and post education groups, they showed statistically significant in anxiety and satisfaction (p<0.05). Moreover, the findings of this study confirmed that video education and information on UGI provided in advance reduce patients' anxiety and increase their satisfaction with examination. 건강검진을 위해 병원을 내원한 수검자 중 위장조영검사를 선택한 수검자를 대상으로 서비스 만족도 개선을 위해 본 연구를 시행하였다. 수검자를 대상으로 설문조사를 시행하였으며, 2014년 5월부터 2개월 동안 내원한 수검자 147명을 교육 전 대상자로, 2014년 7월부터 2개월 동안 내원한 수검자 164명을 교육 후 대상자로 선정하였다. 교육 전 대상자에게 불안감, 설명필요, 설명방식, 조영검사 만족도 등을 조사하여 이를 바탕으로 동영상을 제작하였으며, 교육 후 대상자에게 제공하여 불안감 변화, 동영상 설명 만족도, 도움정도, 재 시청 의향 등을 조사하였다. 교육 전 측정한 평균값은 불안감 2.62, 설명필요성 2.52로 측정 되었으며, 설명방식은 대상자의 78.2%가 설명 안내 동영상을 선택하였고, 조영검사 만족도는 1.55로 조사되었다. 교육 후 측정한 평균값에서 불안감의 변화는 1.45, 동영상설명만족 2.80, 도움정도 2.79, 재 시청 의향은 2.80으로 측정되었다. 교육 전, 후 집단 간 T-test에서 불안감 변화, 만족도 등에서 통계적으로 유의한 차이를 보였으며(p<0.05), 위장조영검사에 대한 동영상 교육을 통한 사전 정보제공이 환자의 불안감을 감소시켰고, 검사만족도는 증가 시켰음을 알 수 있었다.